Fulfilling global marine commitments; lessons learned from Gabon. Issue 3 (1st February 2022) - Metcalfe, Kristian; White, Lee; Lee, Michelle E.; Fay, J. Michael; Abitsi, Gaspard; Parnell, Richard J.; Smith, Robert J.; Agamboue, Pierre Didier; Bayet, Jean Pierre; Mve Beh, Jean Hervé; Bongo, Serge; Boussamba, Francois; et al.
Abstract: As part of the Post‐2020 Biodiversity Framework, nations are assessing progress over the past decade in addressing the underlying drivers that influence direct pressures on biodiversity and formulating new policies and strategies for the decade to come. For marine conservation, global marine protected area (MPA) coverage is still falling short of the 10% target set in 2010. Here we show that while this reflects a lack of progress in many low‐ and middle‐income countries, a few of these nations have met or exceeded international commitments. To provide an in‐depth explanation of how this was achieved in Gabon, we summarize the lessons learnt by our consortium of policy makers and practitioners who helped implement a comprehensive and ecologically representative network of 20 MPAs. We show the importance of creating a national framework, building long‐term stakeholder support, and focusing on research that guides implementation and policy; and outline a four‐step approach that countries and donors could use as an example to help meet international commitments. By responding to calls to share lessons learned to inform future Convention on Biological Diversity targets, we show how Gabon's experiences could inform change elsewhere.